College Algebra 7th Edition

Published by Brooks Cole
ISBN 10: 1305115546
ISBN 13: 978-1-30511-554-5

Chapter 2, Functions - Section 2.8 - One-to-One Functions and their Inverses - 2.8 Exercises: 59

Answer

$f^{-1}(x) = \frac{x - 3}{2 + 5x}$

Work Step by Step

$f(x) = \frac{2x +3}{1 - 5x}$ $y = \frac{2x +3}{1 - 5x}$ y(1- 5x) = 2x + 3 y - 5xy = 2x + 3 y - 3 = 2x + 5xy y - 3 = x(2 + 5y) $x = \frac{y - 3}{2 + 5y}$ $f^{-1}(x) = \frac{x - 3}{2 + 5x}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.